2023
DOI: 10.3390/rs15164042
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Lithosphere–Atmosphere–Ionosphere Coupling Associated with the 2022 Luding Ms6.8 Earthquake

Abstract: Taking the Luding Ms6.8 earthquake (EQ) on 5 September 2022 as a case study, we investigated the potential seismic anomalies of the ionosphere, infrared radiation, atmospheric electrostatic field (AEF), and hot spring ions in the seismogenic region. Firstly, we analyzed the multi-parameter anomalies in the ionosphere around the epicenter and found synchronous anomalous disturbances in the ground parameters, namely the global ionospheric map (GIM), GPS, TEC, and satellite parameters, such as the He+ and O+ dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Zhu et al [57] studied the outgoing longwave radiation (OLR) data prior to the Luding earthquake.Significant OLR anomalies were detected on August 9, August 18, and August 28 before the Luding earthquake. Liu et al [58] also investigated the anomalies in AEF and OLR before the Luding earthquake, along with examining disturbances in the ionosphere and investigating the anomalies in infrared radiation and hot spring ions. They found that the AEF anomalies appeared approximately one week before the earthquake, the (infrared brightness temperature) IBT anomalies showed throughout August, and the anomalies in hot spring ions appeared in July and lasted until September, which may indicate the enhanced seismic-ionospheric coupling effect.…”
Section: Superposed Epoch Analysis (Sea) For the Geomagnetic Topology...mentioning
confidence: 99%
“…Zhu et al [57] studied the outgoing longwave radiation (OLR) data prior to the Luding earthquake.Significant OLR anomalies were detected on August 9, August 18, and August 28 before the Luding earthquake. Liu et al [58] also investigated the anomalies in AEF and OLR before the Luding earthquake, along with examining disturbances in the ionosphere and investigating the anomalies in infrared radiation and hot spring ions. They found that the AEF anomalies appeared approximately one week before the earthquake, the (infrared brightness temperature) IBT anomalies showed throughout August, and the anomalies in hot spring ions appeared in July and lasted until September, which may indicate the enhanced seismic-ionospheric coupling effect.…”
Section: Superposed Epoch Analysis (Sea) For the Geomagnetic Topology...mentioning
confidence: 99%
“…The earthquake reached a ground intensity level of nine, resulting in the loss of 97 lives, with 20 people reported as missing. In a study conducted by Liu et al [43], various geophysical parameters in the ionosphere, infrared radiation, atmospheric elec- On 5 September 2022, at 4:52:18 Universal Time (UT), an earthquake, 6.8 in magnitude, struck near Luding County in Sichuan, China, at the coordinates 102.08 • E, 29.59 • N [41,42]. The earthquake reached a ground intensity level of nine, resulting in the loss of 97 lives, with 20 people reported as missing.…”
Section: Introductionmentioning
confidence: 99%
“…The earthquake reached a ground intensity level of nine, resulting in the loss of 97 lives, with 20 people reported as missing. In a study conducted by Liu et al [43], various geophysical parameters in the ionosphere, infrared radiation, atmospheric electrostatic field, and hot spring ions in the seismogenic region were examined. Pre-earthquake anomalies were observed in the lithosphere-atmosphere-ionosphere coupling approximately 10 days before the Luding earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…Following the launch of the China Seismo-Electromagnetic Satellite (CSES) on February 2, 2018, a series of studies have been conducted in various areas. These include data availability (Yan et al, 2020;Liu et al, 2021), global geomagnetic models , ionospheric events such as magnetic storms (Spogli et al, 2021), statistical characteristics of seismic ionospheric disturbances (Li et al, 2020; De Santis et al, 2021), and multi-layer coupling (Marchetti et al, 2019;Zhao et al, 2021;Liu et al, 2023;.…”
Section: Introductionmentioning
confidence: 99%